Amidoxime uranium adsorbent as well as preparation method and application thereof

The geminoxime-based uranium adsorbent prepared by radical polymerization and hydroxylamine treatment technology solves the problems of unstable chemical structure, low synthesis efficiency and unenvironmental preparation process of the uranium adsorbent in the prior art, and achieves an efficient and environmentally friendly uranium adsorption effect.

CN119771364APending Publication Date: 2025-04-08XIAMEN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510016260.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The existing uranium adsorbents have problems such as unstable chemical structure, low synthesis efficiency and unenvironmental preparation process.

Method used

The cyano-containing porous organic polymer was prepared by a free radical polymerization strategy and treated with a hydroxylamine solution to convert the cyano group into a geminoxime group to prepare a geminoxime uranium adsorbent.

Benefits of technology

It has achieved green and environmentally friendly, easy to operate and stable product structure, and has good uranium ion adsorption performance, with a maximum adsorption capacity of 723 mg g-1.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119771364A_ABST
    Figure CN119771364A_ABST
Patent Text Reader

Abstract

The invention discloses an amidoxime uranium adsorbent and a preparation method and application thereof, and relates to the technical field of adsorbents. Comprising the following steps: 1) adding a cyano-containing electron-deficient monomer, an electron-rich olefin monomer and an initiator into a solvent, then carrying out freezing-vacuumizing-unfreezing-nitrogen charging circulation for several times, then carrying out a stirring reaction and filtering to obtain a solid, extracting with tetrahydrofuran, and carrying out vacuum drying to obtain a cyano-containing porous organic polymer; and (2) adding the cyano-containing porous organic polymer obtained in the step (1) and a hydroxylamine aqueous solution into tetrahydrofuran, carrying out heating reaction, filtering after the reaction is completed to obtain a solid, extracting with ethanol, and finally carrying out vacuum drying to obtain the amidoxime uranium adsorbent. The method is mild in reaction condition and environmentally friendly, and the prepared amidoxime uranium adsorbent is stable in structure and has good uranium ion adsorption performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of adsorbents, and in particular to an amidoxime-based uranium adsorbent and a preparation method and application thereof. Background Art

[0002] Nuclear energy is a clean, low-carbon, high-energy-density energy source that has made important contributions to maintaining global energy security, addressing global climate change, promoting world economic growth, and mitigating climate change. Uranium is an important nuclear fuel, but it is extremely radioactive and chemically toxic. The direct discharge of uranium-containing wastewater without treatment will not only cause serious environmental pollution and biological hazards, but also lead to the loss of uranium resources. Therefore, it is urgent to develop efficient methods to treat and recover uranium in wastewater. The adsorption method is considered to be the most promising strategy due to its simple operation, strong specificity and low cost. Amidoxime groups have a strong affinity for uranyl ions, and amidoxime-based materials are considered to be the most effective uranium adsorbents at present. At present, most amidoxime-based adsorbents are obtained by amidoximation of cyanide-containing materials.

[0003] Among the commonly used adsorbents, porous materials have shown significant advantages. Among them, metal organic frameworks (MOFs) and covalent organic frameworks (COFs) have attracted widespread attention due to their high specific surface area, rich active sites and adjustable pore structure. However, due to the relatively weak and unstable metal-ligand coordination bonds, MOFs have low chemical stability. COFs are connected by stable covalent bonds, but their synthesis usually takes a long time to complete, and the synthesis efficiency is low, which is not conducive to large-scale production and rapid preparation. Hypercrosslinked polymers (HCPs) have the characteristics of mild synthesis conditions, fast reaction speed, and stable chemical structure, and are expected to become an alternative for preparing uranium adsorbent materials. However, HCPs are currently usually prepared using Friedel-Crafts alkylation reactions. In order to achieve a high conversion rate, the reaction requires the addition of a Lewis acid catalyst far exceeding the molar amount, and the Lewis acid is easily hydrolyzed during the reaction to produce corrosive gases, which will inevitably cause serious pollution to the environment. Therefore, it is urgent to develop a green, environmentally friendly, easy-to-operate, and product-stable uranium adsorbent preparation technology to meet actual production needs. Summary of the invention

[0004] The purpose of the present invention is to solve the above problems of unstable chemical structure, low synthesis efficiency and environmentally unfriendly preparation process of uranium adsorbent in the prior art, and to provide a uranium adsorbent and its preparation method and application. The present invention prepares a cyanide-containing porous organic polymer by a free radical polymerization strategy, and then treats it with a hydroxylamine solution to convert the cyanide on the polymer skeleton into an amidoxime group, thereby preparing an amidoxime-based porous organic polymer with an adsorption effect on uranium, that is, an amidoxime-based uranium adsorbent.

[0005] In order to achieve the above object, the present invention adopts the following technical scheme:

[0006] A method for preparing an amidoxime-based uranium adsorbent comprises the following steps:

[0007] 1) Adding a cyano-containing electron-deficient monomer, an electron-rich olefin monomer and an initiator into a solvent, and then freezing-vacuuming-thawing-nitrogen filling for several cycles, followed by stirring for reaction, filtering to obtain a solid, extracting with tetrahydrofuran, and vacuum drying to obtain a cyano-containing porous organic polymer;

[0008] 2) adding the cyanide-containing porous organic polymer obtained in step 1) and the hydroxylamine aqueous solution into tetrahydrofuran, heating for reaction, filtering to obtain a solid after the reaction is completed, extracting with ethanol, and finally vacuum drying to obtain the amidoxime uranium adsorbent.

[0009] In step 1), the electron-deficient cyanide-containing monomer includes at least one of acrylonitrile, fumaronitrile, cinnamonitrile and 7,7,8,8-tetracyanoquinodimethane; and the electron-rich olefin monomer includes at least one of divinylbenzene and divinylbiphenyl.

[0010] In step 1), the molar ratio of the cyanide-containing electron-deficient monomer to the electron-rich olefin monomer is 0.5-3:1.

[0011] In step 1), the amount of the initiator is 1 wt% to 10 wt% of the total mass of the monomers; the ratio of the total mass of the monomers to the volume of the solvent is 10 to 80 mg: 1 mL.

[0012] In step 1), the solvent includes but is not limited to at least one of toluene, 1,4-dioxane, N,N-dimethylformamide, acetonitrile, and N-methylpyrrolidone; the initiator includes an azo initiator (such as azobisisobutyronitrile, azobisisoheptylnitrile, etc.) and a peroxide initiator (such as benzoyl peroxide, diisopropylbenzene peroxide, etc.).

[0013] In step 1), the stirring reaction is carried out at 60-90° C. for 12-24 h.

[0014] In step 2), the mass ratio of the cyanide-containing porous organic polymer, the hydroxylamine aqueous solution and tetrahydrofuran is 1: 5-20: 45-180.

[0015] In step 2), the heating reaction is carried out at 40-65°C for 24-72 hours.

[0016] An amidoxime-based uranium adsorbent is prepared by the above-mentioned preparation method.

[0017] The amidoxime-based uranium adsorbent is used for adsorbing uranium.

[0018] Compared with the prior art, the technical solution of the present invention has the following beneficial effects:

[0019] The present invention provides a green, environmentally friendly, simple to operate and structurally stable uranium adsorbent preparation technology. The preparation technology requires a small amount of initiator, and no by-products are generated during the polymerization process. The preparation process is green and environmentally friendly. The preparation technology provided by the present invention is easy to operate, has mild reaction conditions and a fast reaction speed. The product prepared by the present invention is connected by stable covalent bonds and has a stable structure. The two monomers selected by the present invention have a large difference in polarity and tend to form an alternating copolymer with a predictable molecular structure. Compared with other types of reactions, the product composition is easier to control. The amidoxime-based uranium adsorbent prepared by the present invention has good uranium ion adsorption performance (the maximum adsorption amount can reach 723 mg g -1 ). BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 It is the FT-IR spectrum of the cyano group-containing porous organic polymer described in step 1 of Examples 1 to 6.

[0021] Figure 2 FT-IR spectra of the amidoxime-based uranium adsorbents prepared in Examples 1 to 6.

[0022] Figure 3 It is the adsorption isotherm of the amidoxime-based uranium adsorbent prepared in Examples 1 to 6.

[0023] Figure 4 1 is a pore size distribution diagram of the amidoxime-based uranium adsorbent prepared in Examples 1 to 6.

[0024] Figure 5 1 is a diagram showing the adsorption effect of the amidoxime-based uranium adsorbent prepared in Example 6 on uranium in solutions with different pH values.

[0025] Figure 6 This is a diagram showing the adsorption effect of amidoxime-based uranium adsorbents prepared in Examples 1 to 6 on uranium under the condition of pH=6.

[0026] Figure 7 This is the adsorption isotherm of the amidoxime uranium prepared in Example 6. DETAILED DESCRIPTION

[0027] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention clearer and more understandable, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments.

[0028] Example 1

[0029] Step 1: Add 0.5 mmol fumaronitrile, 1 mmol divinylbiphenyl, 0.075 mmol AIBN and 5 mL 1,4-dioxane into a Shrek tube, and then freeze-vacuum-thaw-nitrogen-filling for three cycles, followed by stirring and reacting at 80 °C for 24 h, filtering to obtain a solid, extracting with tetrahydrofuran for 12 h, and vacuum drying at 80 °C for 12 h to obtain a cyano-containing porous organic polymer (POPs-FN-0.5).

[0030] Step 2: Add 0.1g POPs-FN-0.5, 1mL 50% hydroxylamine aqueous solution and 10mL tetrahydrofuran into a round-bottom flask. Then place it at 65℃ for 72 hours. After the reaction is completed, filter to obtain a solid, extract it with ethanol for 12 hours, and finally vacuum dry it at 80℃ for 12 hours to obtain the amidoxime uranium adsorbent (AO-POPs-FN-0.5).

[0031] Example 2

[0032] Step 1: Add 0.75 mmol fumaronitrile, 1 mmol divinylbiphenyl, 0.08 mmol AIBN and 5 mL 1,4-dioxane into a Shrek tube, and then freeze-vacuum-thaw-nitrogen-filling for three cycles, followed by stirring and reacting at 80 °C for 24 h, filtering to obtain a solid, extracting with tetrahydrofuran for 12 h, and vacuum drying at 80 °C for 12 h to obtain a cyano-containing porous organic polymer (POPs-FN-0.75).

[0033] Step 2: Add 0.1g POPs-FN-0.75, 1mL 50% hydroxylamine aqueous solution and 10mL tetrahydrofuran into a round-bottom flask. Then place it at 65℃ for 72 hours. After the reaction is completed, filter to obtain a solid, extract it with ethanol for 12 hours, and finally vacuum dry it at 80℃ for 12 hours to obtain the amidoxime uranium adsorbent (AO-POPs-FN-0.75).

[0034] Example 3

[0035] Step 1: Add 1 mmol fumaronitrile, 1 mmol divinylbiphenyl, 0.09 mmol AIBN and 5 mL 1,4-dioxane into a Shrek tube, and then freeze-vacuum-thaw-nitrogen-filling for three cycles, followed by stirring and reacting at 80 °C for 24 h, filtering to obtain a solid, extracting with tetrahydrofuran for 12 h, and vacuum drying at 80 °C for 12 h to obtain a cyano-containing porous organic polymer (POPs-FN-1).

[0036] Step 2: Add 0.1g POPs-FN-1, 1mL 50% hydroxylamine aqueous solution and 10mL tetrahydrofuran into a round-bottom flask. Then place it at 65℃ for 72h. After the reaction is completed, filter to obtain a solid, extract it with ethanol for 12h, and finally vacuum dry it at 80℃ for 12h to obtain the amidoxime uranium adsorbent (AO-POPs-FN-1).

[0037] Example 4

[0038] Step 1: Add 1.5 mmol fumaronitrile, 1 mmol divinylbiphenyl, 0.12 mmol AIBN and 5 mL 1,4-dioxane into a Shrek tube, and then freeze-vacuum-thaw-nitrogen-filling for three cycles, followed by stirring and reacting at 80 °C for 24 h, filtering to obtain a solid, extracting with tetrahydrofuran for 12 h, and vacuum drying at 80 °C for 12 h to obtain a cyano-containing porous organic polymer (POPs-FN-1.5).

[0039] Step 2: Add 0.1g POPs-FN-1.5, 1mL 50% hydroxylamine aqueous solution and 10mL tetrahydrofuran into a round-bottom flask. Then place it at 65℃ for 72h. After the reaction is completed, filter to obtain a solid, extract it with ethanol for 12h, and finally vacuum dry it at 80℃ for 12h to obtain the amidoxime uranium adsorbent (AO-POPs-FN-1.5).

[0040] Example 5

[0041] Step 1: Add 2 mmol fumaronitrile, 1 mmol divinylbiphenyl, 0.15 mmol AIBN and 5 mL 1,4-dioxane into a Shrek tube, and then freeze-vacuum-thaw-nitrogen-filling for three cycles, followed by stirring and reacting at 80 °C for 24 h, filtering to obtain a solid, extracting with tetrahydrofuran for 12 h, and vacuum drying at 80 °C for 12 h to obtain a cyano-containing porous organic polymer (POPs-FN-2).

[0042] Step 2: Add 0.1g POPs-FN-2, 1mL 50% hydroxylamine aqueous solution and 10mL tetrahydrofuran into a round-bottom flask. Then place it at 65℃ for 72h. After the reaction is completed, filter to obtain a solid, extract it with ethanol for 12h, and finally vacuum dry it at 80℃ for 12h to obtain the amidoxime uranium adsorbent (AO-POPs-FN-2).

[0043] Example 6

[0044] Step 1: Add 3 mmol fumaronitrile, 1 mmol divinylbiphenyl, 0.09 mmol AIBN and 5 mL 1,4-dioxane into a Shrek tube, and then freeze-vacuum-thaw-nitrogen-filling for three cycles, followed by stirring and reacting at 80 °C for 24 h, filtering to obtain a solid, extracting with tetrahydrofuran for 12 h, and vacuum drying at 80 °C for 12 h to obtain a cyano-containing porous organic polymer (POPs-FN-3).

[0045] Step 2: Add 0.1g POPs-FN-3, 1mL 50% hydroxylamine aqueous solution and 10mL tetrahydrofuran into a round-bottom flask. Then place it at 65℃ for 72h. After the reaction is completed, filter to obtain a solid, extract it with ethanol for 12h, and finally vacuum dry it at 80℃ for 12h to obtain the amidoxime uranium adsorbent (AO-POPs-FN-3).

[0046] Figure 1 FT-IR spectra of the cyano-containing porous organic polymer obtained in step 1 of Examples 1 to 6. All spectra are at 2250 cm -1 The stretching vibration peaks of the cyano group appeared on the left and right, indicating that a copolymerization reaction occurred between fumaronitrile and divinylbiphenyl in step one, and the cyano group was successfully introduced into the skeleton of the porous organic polymer.

[0047] Figure 2 The FT-IR spectrum of the amidoxime-based uranium adsorbent prepared by the present invention is shown in FIG. Figure 2 Can see 2250 cm -1 The cyanide peak at 1650 cm -1 、1318 cm -1 and 918 cm -1 The absorption characteristic peak of amidoxime group appears at , confirming the generation of amidoxime group. At 77.3K, nitrogen isothermal adsorption and desorption test was used to study the pore structure of amidoxime uranium adsorbent prepared in Examples 1 to 6. Figure 3 As shown in the figure, the nitrogen adsorption and desorption isotherms of all adsorbents rise rapidly in the low pressure region (P / P0 < 0.01), indicating that they contain a large number of micropores. At the same time, there are hysteresis loops in the medium pressure region (0.1 < P / P0 < 0.9), indicating the presence of mesopores. The pore size distribution of the adsorbent was calculated using non-local density functional theory (NLDFT) ( Figure 4 ), further confirming the existence of a large number of micropores and mesopores.

[0048] Uranium adsorption test:

[0049] Prepare a 200 mg / L uranium ion solution, and adjust the pH value of the solution between 3 and 8 with nitric acid solution and sodium carbonate solution. Add 5 mg of the amidoxime-based adsorbent (AO-POPs-FN-3) prepared in Example 6 to 20 mL of the uranium ion solution, stir at room temperature until adsorption equilibrium, and filter using a 0.22 μm filter membrane. Measure the uranium ion concentration in the solution before and after adsorption by ultraviolet spectrophotometry, and calculate the adsorption capacity of the amidoxime-based uranium adsorbent according to the following formula:

[0050]

[0051] Note: In the formula, q e is the adsorption capacity (mg / g); C0 is the initial concentration of uranium ions in the solution (mg / L); C e is the concentration of uranium ions in the solution after adsorption (mg / L); V is the volume of the solution; m is the mass of the amidoxime-based uranium adsorbent (g).

[0052] like Figure 5 As shown, the adsorption capacity of AO-POPs-FN-3 was the highest at pH = 6, which was 627 mg / g.

[0053] Prepare a 200 mg / L uranium ion solution, and adjust the pH value of the solution to 6 with nitric acid solution and sodium carbonate solution. Add 5 mg of the amidoxime-based adsorbent prepared in Examples 1 to 6 to 20 mL of the uranium ion solution, stir at room temperature until adsorption equilibrium, and filter using a 0.22 μm filter membrane. Use ultraviolet spectrophotometry to measure the uranium ion concentration in the solution before and after adsorption, and then calculate the adsorption capacity q of the amidoxime-based adsorbent. e , the results are as follows Figure 6 The amidoxime-based uranium adsorbent prepared in Example 6 exhibits the best uranium adsorption effect. The adsorption isotherm of the amidoxime-based uranium adsorbent prepared in Example 6 for uranium ions is shown in FIG. Figure 7 As shown in Figure 2, the adsorption process of uranium ions conforms to the Langmuir model (R 2 = 0.99), with a maximum adsorption capacity of 723 mg g -1 .

Claims

1. A method for preparing an amidoxime-based uranium adsorbent, characterized in that: The following steps are involved: 1) Adding a cyano-containing electron-deficient monomer, an electron-rich olefin monomer and an initiator into a solvent, and then freezing-vacuuming-thawing-nitrogen filling for several cycles, followed by stirring for reaction, filtering to obtain a solid, extracting with tetrahydrofuran, and vacuum drying to obtain a cyano-containing porous organic polymer; 2) adding the cyanide-containing porous organic polymer obtained in step 1) and the hydroxylamine aqueous solution into tetrahydrofuran, heating for reaction, filtering to obtain a solid after the reaction is completed, extracting with ethanol, and finally vacuum drying to obtain the amidoxime uranium adsorbent.

2. The method for preparing an amidoxime-based uranium adsorbent according to claim 1, characterized in that: In step 1), the electron-deficient cyano monomer includes at least one of acrylonitrile, fumaronitrile, cinnamonitrile and 7,7,8,8-tetracyanoquinodimethane; and the electron-rich olefin monomer includes at least one of divinylbenzene and divinylbiphenyl.

3. The method for preparing an amidoxime-based uranium adsorbent according to claim 1, characterized in that: In step 1), the molar ratio of the electron-deficient monomer containing a cyanide group to the electron-rich olefin monomer is 0.5-3:

1.

4. The method for preparing an amidoxime-based uranium adsorbent according to claim 1, characterized in that: In step 1), the amount of the initiator is 1 wt% to 10 wt% of the total mass of the monomers; the ratio of the total mass of the monomers to the volume of the solvent is 10 to 80 mg: 1 mL.

5. The method for preparing an amidoxime-based uranium adsorbent according to claim 1, characterized in that: In step 1), the solvent includes at least one of toluene, 1,4-dioxane, N,N-dimethylformamide, acetonitrile, and N-methylpyrrolidone; and the initiator includes one of an azo initiator and a peroxide initiator.

6. The method for preparing an amidoxime-based uranium adsorbent according to claim 1, characterized in that: In step 1), the stirring reaction is carried out at 60-90° C. for 12-24 h.

7. The method for preparing an amidoxime-based uranium adsorbent according to claim 1, characterized in that: In step 2), the mass ratio of the cyanide-containing porous organic polymer, the hydroxylamine aqueous solution and tetrahydrofuran is 1: 5-20: 45-180.

8. The method for preparing an amidoxime-based uranium adsorbent according to claim 1, characterized in that: In step 2), the heating reaction is carried out at 40-65°C for 24-72 hours.

9. An amidoxime-based uranium adsorbent, characterized in that: Prepared by the preparation method according to any one of claims 1 to 8.

10. The use of the amidoxime-based uranium adsorbent according to claim 9, characterized in that: Used to adsorb uranium.